Scaffold hopping of the SYK inhibitor entospletinib leads to broader targeting of the BCR signalosome - Jorda, Radek; Krajčovičová, Soňa; Králová, Petra; Soural, Miroslav; Kryštof, Vladimír (European journal of medicinal chemistry, 2020)
Spleen tyrosine kinase (SYK) and Bruton's tyrosine kinase (BTK) are attractive targets in human haematological malignancies with excessively activated B-cell receptor (BCR) signalling pathways. Entospletinib is a SYK inhibitor that has been evaluated as a clinical candidate. We designed and prepared five isosteres in which the imidazo[1,2-a]pyrazine scaffold of entospletinib was altered to pyrazolo[3,4-d]pyrimidine, pyrrolo[3,2-d]pyrimidine, imidazo[4,5-b]pyridine, imidazo[4,5-c]pyridine and purine. The last two isosteres were the most potent SYK inhibitors, with IC50 values in the mid-nanomolar range. Importantly, three compounds also inhibited BTK more effectively than did entospletinib. Further experiments then showed that BCR signalling was suppressed in Ramos cells by the potent compounds. Preliminary kinase inhibition screening also revealed LCK and SRC as additional targets. Our results further support the hypothesis that multikinase targeting compounds could produce more robust responses in the treatment of B lymphoid neoplasms.
Keywords: indazoly; signální transdukce; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Protein Kinase Inhibitors; Pyrazines; Phosphorylation; Proto-Oncogene Proteins c-bcr; Indazoles; Signal Transduction; Protein kinase; protoonkogenní proteiny c-bcr; Scaffold hopping; Humans; kinasa Syk; Syk Kinase; Spleen tyrosine kinase; inhibitory proteinkinas; fosforylace; Bruton’s tyrosine kinase; Agammaglobulinaemia Tyrosine Kinase; Selectivity; pyraziny; proteinkinasa BTK; lidé